The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1063/1.4982209
|View full text |Cite
|
Sign up to set email alerts
|

Polarization map of correlated sideband generation in vectorial four-wave mixing

Abstract: Polarization analysis of vectorial four-wave mixing (FWM) in birefringent photonic-crystal fibers reveals physically significant tendencies in the behavior of FWM sideband correlations as a function of fiber birefringence, dispersion, and nonlinearity, as well as the pump intensity and bandwidth. Scanning over this parameter space is shown to steer vectorial FWM from largely decoupled sideband generation by individual polarization modes of the pump to FWM scenarios enabling multipartite entanglement generation. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The importance of the generation of polarization EPs and multipartite photon correlations by FWM as a function of the parameter space was highlighted by Petrov et al in 2017 [58]. They showed that controlling parameters such as the nonlinearity, pump power, and bandwidth measurement filtering creates different regimes that can satisfy important quantum optical applications.…”
Section: Fwm Sources and Spectral Propertiesmentioning
confidence: 99%
“…The importance of the generation of polarization EPs and multipartite photon correlations by FWM as a function of the parameter space was highlighted by Petrov et al in 2017 [58]. They showed that controlling parameters such as the nonlinearity, pump power, and bandwidth measurement filtering creates different regimes that can satisfy important quantum optical applications.…”
Section: Fwm Sources and Spectral Propertiesmentioning
confidence: 99%
“…In recent years, multichannel coincidence counting devices have garnered significant interest for use in the field of quantum information [25][26][27]. One technology used to achieve multi-channel coincidence counting is the FPGA counting board.…”
mentioning
confidence: 99%
“…A dichroic mirror (DM in figure 1) then separates the signal and idler fields, sending them into two detection channels. Each of these fields then passes through additional narrowband bandpass filters (BPF1 and BPF2) for a higher coincidence-to-accidental ratio of photon-pair detection [18].…”
mentioning
confidence: 99%